Anthropogenic Nitrogen Deposition Increases Soil Carbon by Enhancing New Carbon of the Soil Aggregate Formation. Issue 3 (12th March 2019) - Chang, Ruiying; Zhou, Wenjun; Fang, Yunting; Bing, Haijian; Sun, Xiangyang; Wang, Genxu
Abstract: Anthropogenic nitrogen (N) deposition can most likely increase temperate forest soil organic carbon (SOC) storage. Increased SOC is usually suggested to be associated with the suppression of SOC decomposition, which has been hypothesized to be due to the decrease in the activity of lignin‐degrading extracellular enzymes and/or the decrease in soil acidity under N addition. However, the potential mechanism of SOC protection derived from N addition is less understood. Here in a low‐deposition temperate montane forest, short‐term N addition could increase SOC storage in the aggregate fraction but not in the bulk soil. N‐induced SOC accumulation was partly associated with the suppressed SOC decomposition (indicated by lower soil respiration) that resulted from the reduced microbial biomass rather than from decreased lignin‐degrading enzyme activity or from reduced soil acidity. In addition, N addition promoted soil aggregate formation, which could partly suppress SOC decomposition by protecting new carbon that originated from plant litter residue to a greater degree, while dissolved organic carbon retention in the mineral soils played a limited role in the SOC sequestration derived from N addition, at least in the short term. A conceptual model was proposed and highlighted a new underlying mechanism of new carbon protection by enhanced aggregate formation, other than the role of microbial suppression, to explain the positive effect of anthropogenic N deposition on forest SOC. Plain Language Summary: Since the industrial revolution, atmospheric active nitrogen (N) deposition has continued to increase worldwide due to human activities. N is considered as an essential element for ecosystem, and anthropogenic N deposition has been found to influence many aspects of forest ecosystems, such as soil acidity, the fate, cycle, and storage of soil carbon (C). It is very important to understand the changes in forest soil C and the potential mechanisms as forest soil holds a large C storage and plays a significant role in global C cycle and global warming. However, the direct, extent, and mechanism of the effects of N deposition on forest carbon are still unclear. Based on an experimental N‐addition treatment conducted in a montane forest, we found that short‐term N addition could increase soil storage in the aggregate fraction but not in the bulk soil. The N‐induced aggregate C accumulation is associated with the enhanced soil aggregate formation inducing by N addition. Greater aggregate formation could protect greater C in the aggregate from microbial decomposition. This result presents a new conceptual framework regarding interactions between C and N cycling and provides a new insight in the effect of N deposition on soil structure and dynamic of carbon. Key Points: Short‐term N addition increases soil C in aggregate fraction not yet in bulk soil N‐induced enhanced aggregate formation protects more new C from decomposition N‐derived suppressed C decomposition is related to lower microbial biomass